Pengembangan Sistem Informasi Eksekutif Dashboard E-Government Berbasis Android pada Dinas Komunikasi dan Informatika Kabupaten Sidoarjo - Fachry Aditya Rachman; Widhy Hayuhardhika Nugraha Putra; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Department of Communication and Information of Sidoarjo Regency has the duty as the recipient of the Regent of Sidoarjo with the Regional Organization Unit (ROU) regarding the presentment of the government data of each ROU. To this day, the presentment of government data for the Regent of Sidoarjo still uses the traditional way which consumed more energy and more time-consuming because Diskominfo must process the data that was sent by ROU in the form of excel spreadsheet into a certain diagram first so those data can be easily read by the Regent of Sidoarjo. This caused the decision made by the Regent of Sidoarjo to be delayed. Based on these considerations, an Android-based executive information system e-government dashboard is needed so that the government data needed by the Regent of Sidoarjo can be accessed using a mobile application by retrieving the required data on the available data warehouse with the aid of web services. This system development uses a method called the waterfall model. This research resulted in 4 results which are requirement analysis, system planning, system implementation, and system testing. Validation testing, mobile compatibility testing, and user acceptance testing were used in the testing phase. The results of the tests show how the system run under the requirements defined in the analysis phase and show that this system helps the Regent of Sidoarjo to see the government data easier and make an activity out of it if there's a mistake in the data.